Kekayaan Intelektual sebagai Objek Jaminan dalam Pembiayaan Usaha Mikro, Kecil, dan Menengah: Studi Perbandingan Indonesia dan Vietnam - Sri Mulyani; Marwiyah Marwiyah; Le Ho Trung Hieu (SPEKTRUM HUKUM, 2026)
The knowledge-based economy has increased the strategic value of intellectual property (IP) as an economic asset that may be used as collateral for Micro, Small, and Medium Enterprise (MSME) financing. In Indonesia, although several laws and regulations recognize the potential use of IP as collateral, implementation remains limited due to fragmented regulations, the absence of standardized valuation mechanisms, unclear registration and enforcement procedures, and limited confidence among financing institutions in intangible assets. In contrast, Vietnam has developed a more integrated legal and policy framework supporting the economic utilization of IP and improving MSMEs’ access to financing. This study analyzes the legal frameworks governing IP as collateral in Indonesia and Vietnam, identifies their similarities, differences, and regulatory weaknesses, and formulates a legal reform model to strengthen legal certainty and MSME financing access. The study applies normative legal research using statutory, conceptual, and comparative approaches. Legal materials are analyzed qualitatively through descriptive-analytical and comparative methods. The findings show that Indonesia’s regulatory framework remains fragmented and lacks comprehensive valuation, registration, and enforcement mechanisms, while Vietnam provides a more supportive framework for the use of intangible assets in secured transactions. This study proposes an Intellectual Property-Based Secured Financing Model that integrates legal recognition of IP as collateral, standardized valuation, integrated registration, effective enforcement mechanisms, and risk mitigation. The proposed model aims to establish a more effective, equitable, and legally certain framework for IP-based MSME financing.